emteqPRO—Fully Integrated Biometric Sensing Array for Non-Invasive Biomedical Research in Virtual Reality - Gnacek, Michal; Broulidakis, John; Mavridou, Ifigeneia; Fatoorechi, Mohsen; Seiss, Ellen; Kostoulas, Theodoros; Balaguer-Ballester, Emili; Kiprijanovska, Ivana; Rosten, Claire; Nduka, Charles (Frontiers in Virtual Reality, 2022)
Virtual Reality (VR) enables the simulation of ecologically validated scenarios, which are ideal for 18 studying behaviour in controllable conditions. Physiological measures captured in these studies 19 provide a deeper insight into how an individual responds to a given scenario. However, the 20 combination of the various biosensing devices presents several challenges, such as time 21 synchronisation between devices, replication between participants and a cumbersome setup. 22 Additionally, important salient facial information is typically covered by the VR headset, requiring a 23 different approach to facial muscle measurement. These challenges can restrict the use of these 24 devices in laboratory settings. This paper describes a solution to this problem. More specifically, we 25 introduce the emteqPRO system which provides an all-in-one solution for the collection of 26 physiological data through a multi-sensor array built into the VR headset. EmteqPRO is a ready to 27 use, flexible sensor platform enabling convenient, heterogenous and multimodal emotional research 28 in VR. It enables the capture of facial muscle activations, heart rate features, skin impedance and 29 movement data – all important factors in the study of emotion. The platform provides researchers 30 with the ability to monitor data from users in real-time, in co-located and remote set-ups, and to 31 access arousal and valence values computed using machine learning (ML) models via cloud services. 32 The SDK (Software Development Kit), developed specifically for the Unity game engine enables 33 easy integration of the emteqPRO features into VR environments.